A study on the relationship between stock market prices, gross national product (GNP) and balance of payments position / Azlin Abd. Aziz - Abd. Aziz, Azlin (1996)
The main purpose of this study is to determine whether there is any relationship between Kuala Lumpur Stock Exchange Composite Index and macroeconomic variables i.e. Gross National Product(GNP) and Balance Of Payment Position. Literature Review of related studies are discussed in chapter two. Subsequently, chapter three continues with a brief exposure on performance of Malaysian Stock Market and an overview of The Malaysian Economy. A description of Research and Methodology are discussed in chapter four .Data are collected on quarterly basis for a period from January 1986 to 1995. There are 40 observations of each variable. Five empirical findings have been tested with a Multiple Linear Regression and correlation analysis by using Time Series Processor ( TSP). For the analysis carried out, it can be concluded that Kuala Lumpur Stock Exchange Composite Index is positively related to under study variable i.e. Gross National Product (GNP), Balance On current account, Balance On capital Account. However, it is inversely related to Overall Balance Of Payments. The study also indicates that there generally exist a high degree of correlation between KLSE Composite index (KLCI) and other variables.